Case report of huge cervical dumbbell tumor in neurofibromatosis. Give up surgery? - Johari, Joehaimey; Omar, Ahmad Sabri; Hau, Mohammad Anwar; Sharifudin, Mohd Ariff (2011)
A dumbbell-shaped lesion is a solitary tumour that is constricted as it exits the neural foramen. The constriction gives the neurofibroma the appearance of a dumbbell that is used by weight lifters. Neurofibromas that arise from the spinal canal may be intradural or extradural and most commonly in the cervical spine (44%), followed by the thoracic spine (27%) and the lumbar spine (21%). The intraspinal portion of the tumor may cause spinal-cord compression and nerve root failure. The resection of huge dumbbell tumours raises several problems, including preservation of the cervical nerve root, control of the vertebral artery, and maintenance of spine motion, curvature. We report a case of a 14-year-old boy with neurofibromatosis type 1 and intraspinal, extradural tumour of the cervical spine presented with progressive quadriparesis at the level of C3 downward. Surgery was done combined posterior and anterior approach with a 2-stage surgery. The tumour was approached posteriorly in the first surgery, followed by the second surgery from anterior. Duration between the two surgeries was four weeks apart. He showed dramatic recovery immediately following the first surgery and further improved after the second. By the end of two weeks after the second surgery, he was able to manage himself independently, and recovered hi s fine motor functions. Tumour removal by a lateral approach still carries a risk of injuring vital structures. Surgical enucleation of dumbbell cervical tumour in neurofibromatosis gives good prognosis of the recovery despite of the severity of neurology of initial clinical presentation. Two-stage surgery provides safe surgery and minimal morbidity to patient. Technical aspect and advantages are further discussed.